Konflik Batin dan Kebahagiaan Tokoh Malla dalam Cerita Pendek “Kebahagiaan yang Membunuh” Karya Atta Verin Kajian Psikologis - Badriah Badriah; Nori Anggraini (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Literature is not only a source of entertainment, but also a tool for contemplating human life that is full of internal conflicts and psychological issues. Short stories as a type of literature often present the realities of life in a concise yet meaningful way, making them interesting to analyze with a variety of scientific methods. This research focuses on the short story "Happiness That Kills" by applying two main approaches, namely the analysis of intrinsic elements and literary psychology. This story depicts a happy state that appears from the outside, but actually hides the emotional burden experienced by the main character, Malla. The method applied in this study is qualitative descriptive with literature study techniques, which is oriented towards the introduction of themes, plots, characters, settings, and mandates, as well as exploring the psychological dynamics of characters using Freud's psychoanalytic theory. The results of the study show that the internal conflicts in this story arise from the battle between the id, ego, and superego, especially when Malla struggles to maintain harmony in her family at the expense of herself. Overall, this short story shows that forced happiness can lead to suffering. By combining structural and psychological analysis, this study reveals the deep meaning related to social pressures, inner struggles, and humanitarian messages that the author seeks to convey. It is hoped that the results of this research can contribute to the study of literature, especially in understanding the relationship between story structure and the psychological condition of characters in contemporary literary works.